Pemberdayaan Masyarakat Nelayan di Wilayah Pesisir Kecamatan Marusu Kabupaten Maros - Adi Sumandiyar (Indonesian Journal of Community Services, 2022)
This study aims to determine the success of empowering fishing communities in the coastal areas of Marusu District, Maros Regency. This study uses a qualitative descriptive approach, with a multisystemic approach model used to provide an overview of the research location. A qualitative descriptive research approach is used to thoroughly analyze the author's main ideas about the subject in the form of discourse and context of specificity. The results showed that the implementation of empowering fishing communities in the coastal areas of Marusu District, Maros Regency, was by making instruments that regulate the empowerment of fishing communities. This is done to be able to optimize the quality of the coastal environment covering social, economic, and cultural aspects. In addition, the strategy can create an atmosphere conducive to the implementation of development to provide access to various interests of fishing communities to optimize development in coastal areas.